FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG - Sri Lestari Yuli Prastyatini (AKUNTANSI DEWANTARA, 2021)
This study aims to examine the factors that affect the audit report lag. They are size of public accountant, age of the listing company, size of the company, debt to equity ratio, commissioners, and independent commissioner. The population of the study is the property and real estate companies registered in the Indonesia Stock Exchange the period of 2011-2013. Sampling technique employed in this study is the purposive sampling the total sample was 115 financial report of 2011 to 2013. Data processing is performed using multiple linear regression analysis. The result of the study shows that the size of public accountant, size of the company, debt to equity ratio, commissioners, and independent commissioner significantly affect the audit report lag. While the age of listing does not significantly affect the audit report lag.